Recent updates and perspectives on leishmaniasis - Savoia, Dianella (Journal of infection in developing countries, 2015)
Leishmaniasis is a neglected vector-borne tropical infection considered to be a disease of the poor. Concentrated in poverty-stricken countries within Southeast Asia, East Africa, and Latin America, it is also endemic in several Mediterranean countries. The management of the heterogeneous syndromes determined by parasites belonging to the genus Leishmania is particularly difficult in developed, non-endemic countries owing to the unfamiliarity of physicians with clinical symptoms, diagnostic possibilities, and available treatment options. Therefore, travelers and other people who may be exposed to sand flies in endemic areas should receive counseling regarding leishmaniasis and appropriate protective measures. Serological diagnosis is rarely used for cutaneous and mucocutaneous diseases, but it is the most commonly used technique for visceral leishmaniasis. The drugs used to treat this last disease are expensive and sometimes have toxic side effects. This review highlights the diagnostic, chemotherapeutic, and immunizing strategies to control leishmaniasis, though no human vaccine is commercially available currently owing to the complexity of the cellular immune response to this parasite.